2008
DOI: 10.1007/s10765-008-0395-z
|View full text |Cite
|
Sign up to set email alerts
|

Volumetric Properties of the Ionic Liquid, 1-Butyl-3-methylimidazolium Tetrafluoroborate, in Organic Solvents at T =  298.15K

Abstract: Apparent molar volumes, V φ , and compressibilities, κ φ , of 1-butyl-3-methylimidazolium tetrafluoroborate ([BMIm][BF 4 ]) have been determined from precise density and speed-of-sound measurements in organic solvents, methanol (MeOH), acetonitrile (MeCN), tetrahydrofuran (THF), N,N-dimethylacetamide (DMA), and dimethylsulfoxide (DMSO) in the dilute region of the ionic liquid. Corresponding values at infinite dilution are estimated by the Redlich-Mayer and Pitzer equations. The results have been interpreted by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
33
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 52 publications
3
33
0
Order By: Relevance
“…It is known that in several binary mixtures containing RTMS (ionic liquids) the locus of maxima/minima in V E against composition is also away from the equimolar composition. 52 53 In the case of the nitrile solvents mixtures, two major factors can explain the negative excess molar volumes observed. On one hand, the large difference in molar volume of the two components favors the packing of the molecular solvent in the natural cavities existing in the RTMS.…”
Section: Predictive Methodsmentioning
confidence: 99%
“…It is known that in several binary mixtures containing RTMS (ionic liquids) the locus of maxima/minima in V E against composition is also away from the equimolar composition. 52 53 In the case of the nitrile solvents mixtures, two major factors can explain the negative excess molar volumes observed. On one hand, the large difference in molar volume of the two components favors the packing of the molecular solvent in the natural cavities existing in the RTMS.…”
Section: Predictive Methodsmentioning
confidence: 99%
“…The crude product was dissolved in acetonitrile and crystallized by adding dropwise to toluene in an ice bath. The product was dried in high vacuum at 333.15 K using a rotary 1278.62 [36] 1485.12 [36] 1457.30 [42] 1280 [39] 1484.5 l [41] 1283 [40] evaporator for at least 4 h at 0.7 kPa. All the solutions were prepared by mass on a Sartorius CP124S balance precise to within ±10 −4 g. The density and speed of sound of the mixtures were measured at different temperatures with a digital vibrating-tube analyzer (Anton Paar DSA 5000, Austria) with proportional temperature control that kept the samples at the working temperature within ±10 −3 K. The apparatus was calibrated with double-distilled, deionized, and degassed water, and dry air at atmospheric pressure according to the instrument catalog.…”
Section: Methodsmentioning
confidence: 99%
“…As the eld of ILs remains rapidly growing [1][2][3][4][5] and the combined use of ILs with conventional solvents has become more and more popular through all these years, [6][7][8] it is desirable to know some guiding principles regarding the power of solvation varied by the IL-molecular binary solvent, as compared to the situation for single or binary molecular media. However, except for some physical property studies of this category of binary media, [9][10][11][12][13][14] sparse work could be found in the literature reporting their effect on facilitating a chemical process (where bonding situation is changed) such as acidic bond-dissociation. 15 This is quite surprising, since among all kinds of chemical transformations, acidic R-H dissociation in conventional solvents, [16][17][18][19][20] recently also in ionic media, [21][22][23][24][25] oen by means of pK a study, is the most extensively investigated process, which not only laid the foundation for many most inuential physical organic principles, [26][27][28][29] but also provided some quantitative understandings of solvation effects on stabilizing various species generated upon heterolytic bond dissociation.…”
Section: Introductionmentioning
confidence: 99%